Campanha Becks - agência Trampo - Magalhães , Angélica Santana (2021)
The Trampo agency was created in the third semester of the advertising and advertising course at the Cruzeiro do Sul University, in 2019. The small group of students were sitting at the bar table drinking that cold one - the place where their best strategies and stories usually come out - while talking about the path they were going to take: that's how Trampo was born. Coming from the most diverse places in São Paulo, each one has their own journey, but, somehow, they think together and, above all, they think outside the box. Getting out of the box for Trampo is understanding the problem and applying a solution that no one thought of before; it's doing more than imaginable freely and out of common sense, planning every step to be taken. That's what Trampo stands for.